2017
DOI: 10.1590/1981-5794-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

Objetivismo/Subjetivismo Em Artigos Científicos Das Diferentes Áreas: A Heterogeneidade Da Escrita Acadêmica

Abstract: ■ ABSTRACT: This paper is aimed at discussing the homogenization of scientific and academic writing in the process of text constitution, by analyzing aspects related to objectivism and subjectivism in academic texts. The selection of some A1 Brazilian scientific articles from different fields of knowledge was carried out according to specific genre: compositional form, style and theme which delimit texts in terms of objectivism and subjectivism. The work is guided by the dialogic assumptions of the Bakhtin's C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Jovens estudantes universitários já se deparam com obstáculos no campo acadêmico, principalmente pela necessidade de aprendizado de novas formas de gêneros e linguagens, o que ainda se torna maior para estudantes com idade mais avançada (ALVES; MOURA, 2016; ALMEIDA, PAN, 2017;FUZA, 2017;ZONTA, 2022), já que as condições de vida dos estudantes mais velhos tendem a ser diferentes dos jovens universitários, pois estão afastados do ambiente acadêmico por mais tempo, tem maiores responsabilidades financeiras, além de vivências com as relações maiores. Tudo isso acaba levando a rotina universitária a impactar de maneira diferente e, consequentemente, exigindo um enfrentamento diferente.…”
Section: Desafios E Novas Tecnologias No Ensino/pesquisa/extensãounclassified
“…Jovens estudantes universitários já se deparam com obstáculos no campo acadêmico, principalmente pela necessidade de aprendizado de novas formas de gêneros e linguagens, o que ainda se torna maior para estudantes com idade mais avançada (ALVES; MOURA, 2016; ALMEIDA, PAN, 2017;FUZA, 2017;ZONTA, 2022), já que as condições de vida dos estudantes mais velhos tendem a ser diferentes dos jovens universitários, pois estão afastados do ambiente acadêmico por mais tempo, tem maiores responsabilidades financeiras, além de vivências com as relações maiores. Tudo isso acaba levando a rotina universitária a impactar de maneira diferente e, consequentemente, exigindo um enfrentamento diferente.…”
Section: Desafios E Novas Tecnologias No Ensino/pesquisa/extensãounclassified
“…Oshodi and colleagues explored leader support and related effects on a culture of safety and found a high degree of importance (≥.8 factor load) for questions specific to communication 8. Other concepts associated with nurse leader communication include nurse satisfaction, turnover, and quality 3,6,7,13. Leadership support was determined to be vital when implementing evidence-based practice 24.…”
Section: Implications For Nursing Leadershipmentioning
confidence: 99%
“…Nurse leaders must communicate vital information to direct care nurses and others to deliver quality healthcare. Fuza postulated that the spoken word has a higher presence of subjectivism than the written word 3. A study found that informal conversations were less susceptible to subjective interpretation than formal conversations 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se para estudantes universitários(as) a apropriação do campo discursivo acadêmico com frequência se realiza por meio de laboriosos obstáculos, principalmente por exigir o aprendizado de novas formas de linguagem, gêneros e práticas de letramento (Almeida & Pan, 2017;Alves & Moura, 2016;Fiad, 2011;Fuza, 2017), para estudantes com mais idade o desafio enfrentado pode ser ainda maior. Como parte desse novo campo, os processos de ensinar e aprender envolvem novas e complexas tecnologias de informação e de comunicação que medeiam as práticas de letramento na universidade.…”
Section: O Mundo Virtual E Os Desafios Tecnológicos Do Novo Campo Dis...unclassified